(untitled) (Journal of actual problems of jurisprudence, 2020)
The study is devoted to the study of the significance and determination of the role of an expert’s opinion on the results of a criminalistic examination as evidence in a criminal trial. In the course of the study, we pursued the following goals: definition of the concept of evidence in criminal proceedings; study of the role of expert opinion in criminal proceedings; highlighting the significance of the conclusion of the forensic examination as evidence, designating the main trends in the use of the conclusion for the prevention of crime. During the study, the features of conducting forensic examinations in the criminal process of the Republic of Kazakhstan were revealed. The practical significance consists in determining the practical significance of the expert’s opinion on the results of the forensic examination for the disclosure of criminal cases. It should also be noted that the work outlines the main trends in the prevention of offenses with the help of a qualitative analysis of expert opinions. During the study, the following methods were used: dialectical method; analysis, synthesis, comparative – legal, private law. Based on the results of the research work, the main trends in the use of forensic expertise to identify the circumstances of the case were identified. The research work makes a significant contribution to the development of the role of forensics in criminal proceedings. Research work has proven its practical value. Key words: examination, evidence, expert, criminal process, crime.